2011
DOI: 10.21236/ada548770
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration/Validation of the Snap Sampler

Abstract: This research was conducted at two sites: the former Pease Air Force Base (AFB) in Portsmouth, NH and the former McClellan AFB in Sacramento, CA. There were ten sampling events at each site and each monitoring well was sampled using Snap Samplers, Regenerated Cellulose (RGC) passive diffusion samplers, and the EPA's low-flow purging and sampling protocol. Analytes included a broad range of inorganic analytes, and VOCs at the McClellan site. The Snap Sampler was able to provide samples with equivalent concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Several studies (e.g., Vroblesky 2001;Parker and Clark 2004) have shown that the PDB samplers can provide quality data and equivalent analyte concentrations of most volatile organic compounds (VOCs) when compared with the conventional low-flow purging and sampling method. In most instances, findings from other studies conducted using the Snap Sampler (Parker and Mulherin 2007;Parker et al 2009Parker et al , 2011aParker et al , 2011b and the regenerated-cellulose membrane (or dialysis membrane) sampler (Imbrigiotta and Trotsky 2010Imbrigiotta et al 2007) also yielded quality data and comparable analyte concentrations to the low-flow sampling method for a variety of inorganic and organic analytes. Where the use of passive sampling is appropriate, dataquality improvements can also include better delineation of contamination with depth within the screened zone, such as shown by Vroblesky and Peters (2000), Vroblesky and Petkewich (2000), and Vroblesky et al (2003).…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Several studies (e.g., Vroblesky 2001;Parker and Clark 2004) have shown that the PDB samplers can provide quality data and equivalent analyte concentrations of most volatile organic compounds (VOCs) when compared with the conventional low-flow purging and sampling method. In most instances, findings from other studies conducted using the Snap Sampler (Parker and Mulherin 2007;Parker et al 2009Parker et al , 2011aParker et al , 2011b and the regenerated-cellulose membrane (or dialysis membrane) sampler (Imbrigiotta and Trotsky 2010Imbrigiotta et al 2007) also yielded quality data and comparable analyte concentrations to the low-flow sampling method for a variety of inorganic and organic analytes. Where the use of passive sampling is appropriate, dataquality improvements can also include better delineation of contamination with depth within the screened zone, such as shown by Vroblesky and Peters (2000), Vroblesky and Petkewich (2000), and Vroblesky et al (2003).…”
Section: Introductionmentioning
confidence: 84%
“…Cost reductions associated with passive sampling methods result from reduced labor during sampling, reduced equipment costs, and a reduced volume of purge water waste. As examples, Parsons (2003Parsons ( , 2005, Trotsky (2010, 2011b), and Parker et al (2009and Parker et al ( , 2011aand Parker et al ( , 2011b have reported cost savings of 46% to 70% for several types of passive sampling methods.…”
Section: Introductionmentioning
confidence: 99%
“…Low‐flow methods have been shown to yield samples with low turbidities and reproducible levels of metals and PAHs (Kearl et al ; Puls and Powell ; Puls et al ; Backhus et al ). More recently, research studies have examined the use of passive sampling methods (Vroblesky and Hyde ; Vroblesky and Peters ; Vroblesky and Petkewich ; Vroblesky ; Parsons ; Imbrigiotta et al ; Parker et al ).…”
Section: Introductionmentioning
confidence: 99%